Widefield Optical Coherence Tomography Angiography in Diabetic Retinopathy - Alessia Amato; Francesco Nadin; Federico Borghesan; Maria Vittoria Cicinelli; Irini Chatziralli; Saena Sadiq; Rukhsana Mirza; Francesco Bandello (Journal of Diabetes Research)
Purpose. To summarize the role of widefield optical coherence tomography angiography (WF-OCTA) in diabetic retinopathy (DR), extending from the acquisition strategies to the main clinical findings. Methods. A PubMed-based search was carried out using the terms “Diabetic retinopathy”, “optical coherence tomography angiography”, “widefield imaging”, and “ultra-widefield imaging”. All studies published in English up to August 2020 were reviewed. Results. WF-OCTA can be obtained with different approaches, offering advantages over traditional imaging in the study of nonperfusion areas (NPAs) and neovascularization (NV). Quantitative estimates and topographic distribution of NPA and NV are useful for treatment monitoring and artificial intelligence-based approaches. Curvature, segmentation, and motion artifacts should be assessed when using WF-OCTA. Conclusions. WF-OCTA harbors interesting potential in DR because of its noninvasiveness and capability of objective metrics of retinal vasculature. Further studies will facilitate the migration from traditional imaging to WF-OCTA in both the research and clinical practice fields.